GLF partners make the connections an invitation - Weigelt, Jes; Simons, Tony; Frick, Martin; Louman, Bastiaan (2022)
The Institute for Advanced Sustainability Studies e.V., World Agroforestry Center, FAO and CATIE on behalf of the Association of International Research and Development Centers for Agriculture (AIRCA), telling us how a landscapes approach can balance competing resource demands, reverse land degradation, enhance food security and nutrition, and support climate change resilience.